International Disputes and Cultural Ideas in the Canadian Arctic - Burke, Danita Catherine. author. aut Link
XV, 244 p. 8 illus., 6 illus. in color.
Keywords: “Today, when much IR literature about Arctic affairs focuses on the regional level, and where ‘governance’ is something of a buzzword, Danita Catherine Burke’s book offers a fresh alternative. If you want to understand Canada’s approach to the Arctic, Burke argues, you have to acknowledge the importance of cultural and political ideas that play out on the domestic level. After reading this book, I am convinced she is right.” Stian Bones, Professor of History, UiT The Arctic University of Norway “Dr. Burke’s work serves to correlate a burgeoning Canadian identity with the momentum of history viewed across the growing awareness of a young nation’s respons ibilities in its own back yard. She posits an evolving grasp of the Arctic within the hearts and minds of the Canadian Citizen. It is this burgeoning awareness within the Public Square, to claim sovereignty within and beyond the cold and remote icescape of the North, which ultimately defines Canada’s Crown Jewel.” Ken Hedges, FRGS This book explores the Canadian relationship with its portion of the Arctic region which revolves around the dramatic split between the appearance of absent-minded governance, bordering on indifference toward the region, and the raging nationalism during moments of actual and perceived challenge toward the sovereignty of the imagined “Canadian Arctic region.” Canada’s nationalistic relationship with the Arctic region is often discussed as a reactionary phenomenon to the Americanization of Canada and the product of government propaganda. As this book illustrates, however, the complexity and evolution of the Canadian relationship with the Arctic region and its implication for Canada’s approach toward international relations requires a more in-depth exploration.